2010
DOI: 10.1152/ajpcell.00341.2009
|View full text |Cite
|
Sign up to set email alerts
|

Collagen I matrix turnover is regulated by fibronectin polymerization

Abstract: Extracellular matrix (ECM) remodeling occurs during normal homeostasis and also plays an important role during development, tissue repair, and in various disease processes. ECM remodeling involves changes in the synthesis, deposition, and degradation of ECM molecules. ECM molecules can be degraded extracellularly, as well as intracellularly following endocytosis. Our data show that the ECM protein fibronectin is an important regulator of ECM remodeling. We previously showed that agents that inhibit the polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 72 publications
1
70
0
Order By: Relevance
“…The endocytosis and trafficking of ECM receptors, particularly that of the integrins, have been studied extensively and are known to play important roles in cytokinesis and cell migration (Caswell et al, 2009). Among ECM molecules, fibronectin, collagen-I and vitronectin have been reported to undergo endocytosis, with internalization mediated, in part, by the integrins (Madsen et al, 2011;Memmo and McKeown-Longo, 1998;Shi et al, 2010;Shi and Sottile, 2008;Sottile and Chandler, 2005). However, the endocytosis and trafficking of laminins and other basement membrane proteins is not understood at the level of mediators, pathways or biological significance, despite these being crucial structural and signaling molecules that contact the majority of cells in metazoans (Yurchenco, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The endocytosis and trafficking of ECM receptors, particularly that of the integrins, have been studied extensively and are known to play important roles in cytokinesis and cell migration (Caswell et al, 2009). Among ECM molecules, fibronectin, collagen-I and vitronectin have been reported to undergo endocytosis, with internalization mediated, in part, by the integrins (Madsen et al, 2011;Memmo and McKeown-Longo, 1998;Shi et al, 2010;Shi and Sottile, 2008;Sottile and Chandler, 2005). However, the endocytosis and trafficking of laminins and other basement membrane proteins is not understood at the level of mediators, pathways or biological significance, despite these being crucial structural and signaling molecules that contact the majority of cells in metazoans (Yurchenco, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…MT1-MMP is involved in turnover and endocytosis of matrix collagen I, but not matrix fibrinogen Our previous data showed that loss of ECM fibronectin results in the loss of several other proteins from the ECM, including collagen I (Shi et al, 2010;Sottile and Hocking, 2002). Therefore, we investigated whether MT1-MMP is involved in turnover of other ECM proteins.…”
Section: Mt1-mmp Is Involved In Ecm Fibronectin Turnover and Endocytosismentioning
confidence: 94%
“…Texas Red, Alexa-Fluor-488-and AlexaFluor-633-conjugated fibronectins were made according to the manufacture's protocol (Molecular Probes/Invitrogen). Texas Red-conjugated collagen I was made as described previously (Shi et al, 2010). pUR4, a fibronectin polymerization inhibitor, was prepared as described previously (Chiang et al, 2009).…”
Section: Immunological Reagents Chemicals and Proteinsmentioning
confidence: 99%
“…4). Collagen phagocytosis has been studied through the use of collagen-coated beads or native fibrillar collagen (156) and is dependent on the ␣ 2 ␤ 1 integrin (3,24,93). Fibroblasts using this integrin receptor bind and internalize collagen through a Gelsolin-and Racdependent pathway (2).…”
Section: Intracellular Pathway Of Collagen Degradationmentioning
confidence: 99%